PENGARUH HARGA MINYAK DUNIA, INFLASI, PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN DI INDONESIA - Ayu Dinata, Silvia Sefrefita; Idris, Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstract: This study describes the Effect of World Oil Prices, Inflation andEconomic Growth in Indonesia. This study uses time series data from 1978-2019,with multiple linear regression analysis method. Data sources are from the CentralStatistics Agency, BP Statistical, Indonesia Bank and World Bank. The result of thestudy explain that (1) World Oil Prices have a positive and significant effect onunemployment in Indonesia (2) Inflation has a negative and insignificant effect onunemployment in Indonesia (3) Economic Growth has a negative and insignificanteffect on unemployment in Indonesia.Keywords: Unemployment, world oil price, inflation, economic growth